Morphology of the digestive tract of Barbus xanthopterus and Ctenopharyngodon idella: Ali J. Shubber and Abdulmotalib J. Al-Rudainy - Al-Rudainy, Abdulmotalib J. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study is to detected the morphology of the alimentary canal in twofreshwater fish species, Gattan Barbus xanthopterus and Grass carp Ctenopharyngodo idellawhich belonged to cyprinidae.. Increasing in mouth width with body length. Generallypharyngeal teeth arranged according to the following formulas. Gattan : 4-3-2 and 2-3-4Grass carp: 2-5 and 4-2. Variations in the shape, size of pharyngeal teeth were noticed. Theyappear short and wide compact in gattan, but hard and serrated, comb like in grass carp.Different intestinal length were seen indicating differ in feeding natures.